The price of gold in the year 2000: A forecast - A. Pouris (South African Journal of Business Management, 1986)
In this article, two of the most recent efforts to forecast the price of gold are discussed and a prediction for the year 2000 is provided. The forecast is based on the hypothesis that in the long run, commodity prices follow a well-defined path, which permits only gradual and slow changes. The analysis shows that the current price of gold (1985) in terms of US dollars, coincide with the long run equilibrium price simulated by the model. The forecast for the year 2000 suggests that the expected price is US 420 per fine ounce in 1983 constant dollars.
Keywords: 650